TINJAUAN YURIDIS ALIH FUNGSI MOBIL PRIBADI MENJADI ANGKUTAN UMUM BERDASARKAN UNDANG UDANG NOMOR 22 TAHUN 2009 TENTANG LALU LINTAS DAN ANGKUTAN JALAN - Ajay Depkhan (Universitas 17 Agustus 1945 Samarinda, 2020)
AbstractBased on Law Number 22 of 2009 concerning Road Traffic and Transportation, the operation of transportation must have a permit which is explained in Article 173, Formulation of the problem, namely: How is the procedure of using personal cars into public transportation related to the conversion of private cars into public transportation and whatever sanctions for the use of private cars that are used as public transportation that do not have official permission. The normative juridical approach method, the data source, namely primary data from Law Number 22 of 2009 concerning Road Transport and Traffic, and the Head of the Samarinda public transportation section, secondary data derived from literature related to the conversion of private cars into public transportation. The data collection technique was in the form of interviewing respondents from the head of public transport transportation at the Samarinda City Transportation Agency. The research data was analyzed descriptively qualitatively. The results of the study, procedures for transferring private cars to public transportation include: registering private cars at the Transportation Agency to transport passengers by completing requirements, namely: Technical feasibility requirements and filling in permission forms to change the nature / form, roadworthiness requirements, route permit requirements. sanctions for the use of private vehicles (cars) that are used as public ownership that do not have official permits include: criminal sanctions with penalties for vehicle lifting, confinement or fines.